The Influence of Motivation, Work Discipline, and Work Environment on Employee Job Satisfaction - Kamban, Novrianti; Hadiyatno, Didik; Cipto, Rahajeng C Putri (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study was to determine the effect of motivation, work discipline, and work environment on job satisfaction of employees of the Youth, Sports and Tourism Office of Balikpapan City . In this study, there was a population of 70 employees and a sample of 34 respondents . The method used in this study was a statistical test with primary data from the distributed questionnaire . Data analysis used SmarPLS. The results of the study showed that the variables partially Motivation and work environment have no effect, while work discipline has a positive effect on employee job satisfaction.